2015
DOI: 10.1016/j.febslet.2015.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Improved O2‐tolerance in variants of a H2‐evolving [NiFe]‐hydrogenase from Klebsiella oxytoca HP1

Abstract: a b s t r a c tIn this study, we investigated the mechanism of O 2 tolerance of Klebsiella oxytoca HP1 H 2 -evolving hydrogenase 3 (KHyd3) by mutational analysis and three-dimensional structure modeling. Results revealed that certain surface amino acid residues of KHyd3 large subunit, in particular those at the outer entrance of the gas channel, have a visible effect on its oxygen tolerance. Additionally, solution pH, immobilization and O 2 partial pressure also affect KHyd3 O 2 -tolerance to some extent. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Typhimurium (84,237,238,294,295). However, this process has also been experimentally observed in other pathogenic Enterobacteriaceae, notably Enterobacter aerogenes (296-299), K. pneumoniae (254,258,300,301), K. oxytoca (302), and Citrobacter freundii (258,303,304).…”
Section: H 2 Production In Pathogens Bacteriamentioning
confidence: 91%
“…Typhimurium (84,237,238,294,295). However, this process has also been experimentally observed in other pathogenic Enterobacteriaceae, notably Enterobacter aerogenes (296-299), K. pneumoniae (254,258,300,301), K. oxytoca (302), and Citrobacter freundii (258,303,304).…”
Section: H 2 Production In Pathogens Bacteriamentioning
confidence: 91%
“…[10][11][12] Furthermore, hydrogenases may or may not be tolerant to impurities such as CO. [13][14][15][16] Finally, their stability to aerobic oxygen represents the major challenge, 16,17 but a number of hydrogenases are quite tolerant to it. 8,16,[18][19][20][21][22][23][24][25][26] Unfortunately, an enzyme combining all of those favorable properties is yet to be discovered or engineered.…”
Section: Introductionmentioning
confidence: 99%
“…In that work, Huang et al [28] observed a slight increase in the air-stability of a purified G50C G120C double variant K. oxytoca Hyd-3, however a G131C variant was not tested to allow a direct comparison here. Engineering of the K. oxytoca HycE subunit, the Hyd-3 catalytic subunit, has also been reported [29]. In this case, substitution of HycE G300, predicted to be located within a gas channel leading to and from the active site, with either glutamic acid or methionine lead to increased airstability of K. oxytoca Hyd-3 [29].…”
Section: Engineering Air-stability Into Fhlmentioning
confidence: 91%
“…Engineering of the K. oxytoca HycE subunit, the Hyd-3 catalytic subunit, has also been reported [29]. In this case, substitution of HycE G300, predicted to be located within a gas channel leading to and from the active site, with either glutamic acid or methionine lead to increased airstability of K. oxytoca Hyd-3 [29].…”
Section: Engineering Air-stability Into Fhlmentioning
confidence: 91%